2009
DOI: 10.1242/jcs.034827
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Thy-1 induces astrocyte adhesion by engaging syndecan-4 in a cooperative interaction with αvβ3 integrin that activates PKCα and RhoA

Abstract: Clustering of αvβ3 integrin after interaction with the RGD-like integrin-binding sequence present in neuronal Thy-1 triggers formation of focal adhesions and stress fibers in astrocytes via RhoA activation. A putative heparin-binding domain is present in Thy-1, raising the possibility that this membrane protein stimulates astrocyte adhesion via engagement of an integrin and the proteoglycan syndecan-4. Indeed, heparin, heparitinase treatment and mutation of the Thy-1 heparin-binding site each inhibited Thy-1-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
140
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(148 citation statements)
references
References 60 publications
8
140
0
Order By: Relevance
“…3). It was reported that Thy-1 contains a putative polycationic heparin-binding sequence, which mediates binding to the HSPG, Syn4, and activation of PKCa 7 . When K562 cells were pretreated with heparinase (HPSE) to cleave heparin sulphate glycosaminoglycans (GAGs) from the cell surface, adhesions were reduced; Syn4 knockdown by small interfering RNA (siRNA) showed similar reduction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3). It was reported that Thy-1 contains a putative polycationic heparin-binding sequence, which mediates binding to the HSPG, Syn4, and activation of PKCa 7 . When K562 cells were pretreated with heparinase (HPSE) to cleave heparin sulphate glycosaminoglycans (GAGs) from the cell surface, adhesions were reduced; Syn4 knockdown by small interfering RNA (siRNA) showed similar reduction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thy-1 (CD90) is a heavily N-glycosylated single v-type immunoglobulin (Ig) domaincontaining glycoprotein, probably of primordial origin within the immunoglobulin superfamily 2 . It is linked to the outer leaflet of the plasma membrane via a carboxy-terminal glycophosphatidylinositol anchor, where it binds integrins in a variety of tissue-specific contexts, including a M b 2 (Mac-1) on leukocytes 3,4 , a v b 3 on melanoma cells 5 and neurons 6,7 , and a v b 5 on lung fibroblasts 8 . For a full review, see ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thy-1, an abundant mammalian glycoprotein described initially 50 years ago (Barker and Hagood, 2008;Morris, 1992), is expressed in T cells, activated endothelial cells and neurons (Lee et al, 1998;Williams, 1976), and acts in trans as a ligand for avb3 integrin and syndecan-4 on astrocytes (Avalos et al, 2004;Avalos et al, 2009;Leyton et al, 2001). Binding of Thy-1 to both avb3 integrin and syndecan-4 in astrocytes triggers tyrosine phosphorylation of focal adhesion (FA) proteins, activation of protein kinase Ca (PKCa), RhoA and its effector p160ROCK, thereby increasing astrocyte adhesion to the extracellular matrix (Avalos et al, 2004;Avalos et al, 2002;Avalos et al, 2009;Hermosilla et al, 2008;Leyton et al, 2001).…”
Section: Introductionmentioning
confidence: 99%